Comparative study of digestive cells in different midgut regions of stingless bees (Hymenoptera: Apidae: Meliponinae) - Serrao, J. E.; daCruzLandim, C. (Assn Advan Zoology, 1996)
Ultrastructure of the digestive cells was analyzed in three midgut regions (anterior, middle and posterior) of stingless bees. Variations occurs in the presence of lipid inclusions in the cells from posterior midgut and presence of double-membraned vesicles associated to microvilli in the anterior midgut. However, basal plasmic membrane infoldings and augmentation of surface area achieved by microvilli ale very similar in all midgut regions. These results not supported the existence of fluid fluxes in the ectoperitrophic space and suggest that digestive cells in stingless bees are polifunctional, that is, there is not midgut region specialized in secretion ol absorption as observed in other insects.